A step change model analysis of the establishment of pill testing in one Australian jurisdiction - David Caldicott; Toni Makkai; Malcolm McLeod; Stephanie Tzanetis; Gino Vumbaca (BMC, 2023)
Abstract This paper applies the theory of change model (Kotter in Harv Bus Rev 2:59-67, 1995; Moore et al. in Viet Nam J Public Health 1(1):66-75, 2013) to describe the pathway that lead to Australia's first pill testing/drug checking services in Canberra, in the Australian Capital Territory. The paper takes each step of the model and illustrates the key activities that largely occurred over an approximately 24 month period resulting in the service being operational on 29 April 2018. The paper demonstrates that leadership, advocacy and activism are key components, alongside evidence, to bringing about public policy change. It provides a unique insight to the extensive efforts undertaken to achieving the first legally sanctioned pill testing at festivals in Australia and provides a positive case study for those seeking to introduce contested harm reduction services in the drug and alcohol field.